Kultur Campuran dan Faktor Lingkungan Mikroorganisme yang Berperan dalam Fermentasi âTea-Ciderâ - Pingkan Aditiwati; Kusnadi Kusnadi (Institute for Research and Community Services (LPPM) ITB, 2003)
Tea is agricultural product containing beneficial substances, especially used for human health. The study of